GE_GERICHTE C/23991/2011 vom 14. Februar 2014 - GE Cour de justice (2014)
DOL(VICE DU CONSENTEMENT); DOMMAGES-INTÉRÊTS; RECONNAISSANCE DE DETTE | CO.23; CO.28.1; CO.31; CO.320.3; CO.321a.1; CO.321a.3; CO.17